Research status of the relationship between microecological imbalance and lung cancer - Jin, Xin; Gu, Yangang; Song, Xiaojie (Frontiers in Microbiology, 2025)
Microecology refers to the ecosystem formed by human and microbial communities in the process of co-evolution, the microecological imbalance is associated with occurrence and development of multiple diseases, including lung cancer. In this review, we detailedly summarized the concept and roles of microecology, the relationship between microecology and human diseases, and related techniques in microecology studies. Importantly, we specially analyzed the correlations between microecology and lung cancer by focusing on gut microbiota, oral microbiota and lower respiratory tract microbiota, and further evaluated the effects of microbiota dysbiosis on chemotherapy and immunotherapy efficacy in lung cancer. At last, we discussed the potential mechanisms by which dysregulated microbiota promotes the genesis and development of lung cancer. Microecology-centered detection and intervention will improve the early diagnosis of lung cancer and provide new targets for the treatment of lung cancer.